A study of non-extensivity in the Earth’s magnetosphere - Balasis, G.; Eftaxias, K. (The European physical journal. ST, Special topics, 2009)
Magnetic storms are undoubtedly among the most important phenomena in space physics and also a central subject of space weather. The non-extensive Tsallis entropy has been recently introduced, as an effective complexity measure for the analysis of the geomagnetic activity D st index. Tsallis entropy has been shown to sensitively detect the complexity dissimilarity between pre-storm activity and intense magnetic storms in the Earth’s magnetosphere. Here, we show that the D st time series obey a modified form of the Gutenberg-Richter law for the case of non-extensive statistics, thus providing evidence for universality in magnetic storm and earthquake occurrence.